1986
DOI: 10.1002/tera.1420340106
|View full text |Cite
|
Sign up to set email alerts
|

Developmental anomalies induced by all‐trans retinoic acid in fetal mice: I. Macroscopic findings

Abstract: The administration of a single dose of all-trans retinoic acid on day 8 of gestation to pregnant mice, ICR strain, led to malformed fetuses in all of the litters. All-trans retinoic acid (RA) was dissolved in olive oil and given in doses of 60 or 40 mg/kg of body weight. The control mice were given vehicle alone. Examination on day 18 of gestation of the fetuses exposed to 60 mg/kg showed various malformations, such as exencephaly, exophthalmus, micrognathia, agnathia, cleft palate, cleft lower lip, spina bifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 13 publications
3
39
0
1
Order By: Relevance
“…The tissue distribution of CRABP and CRBP transcripts that we have found are in good correlation with the spectrum of tissues affected teratogenically by retinoic acid and retinol in embryos of different species (1,(12)(13)(14)(15)(30)(31)(32)(33)(34). CRABP and CRBP transcripts were found in the limb, spinal cord, brain, and facial structures, which all are well-known teratogenic targets of retinoic acid and retinol.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The tissue distribution of CRABP and CRBP transcripts that we have found are in good correlation with the spectrum of tissues affected teratogenically by retinoic acid and retinol in embryos of different species (1,(12)(13)(14)(15)(30)(31)(32)(33)(34). CRABP and CRBP transcripts were found in the limb, spinal cord, brain, and facial structures, which all are well-known teratogenic targets of retinoic acid and retinol.…”
supporting
confidence: 70%
“…In mouse embryos, it has been reported that hypervitaminosis A causes alterations in the cell cycle of neuroepithelial cells and prevents the closure of the neural tube, producing brain deformities (12,13). Excess vitamin A also alters the pattern of migration of cranial neural crest cells, producing facial skeleton deformities (cleft palate) (14,15). Alterations in the cephalic mesoderm, the axial nonsegmented mesoderm, and finally the segmented mesoderm, especially the somites (rib defects and vertebral malformations), are also caused by administration of excess vitamin A (16,17).…”
mentioning
confidence: 99%
“…In mice, retinoic acid gave craniofacial malformations similar to those seen in rats subjected to maternal diabetes [11,33]. Of note, neuroepithelial cell death and aberrant neural crest-cell migration has been shown to contribute to facial malformations induced by ethanol [34,35] and retinoic acid [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the diverse teratogenic effects on embryos by RA exposure depend on the developmental stage when RA is administered and the dosage of RA (Yasuda 1986;Kessel and Gruss 1991;Kessel 1992). We chose to use a low dose (10 mg of all-trans RA/kg of body weight) to treat E8.5 embryos because under this condition RA almost exclusively affects the patterning of the vertebrae without any effect on the development of the heart, lung, and other visceral organs as well as craniofacial bones.…”
Section: Synergistic Effects Of Ra-treatment and Actriib Mutation On mentioning
confidence: 99%